Impact of COVID-19 during pregnancy on placental pathology, maternal and neonatal outcome – A cross-sectional study on anemic term pregnant women from a tertiary care hospital in southern India - Surekha, M. V.; Suneetha, N.; Balakrishna, N.; Putcha, Uday Kumar; Satyanarayana, K.; Geddam, J. J. Babu; Sreenu, Pagidoju; Tulja, B.; Mamidi, Raja Sriswan; Rutter, Guy A.; Meur, Gargi (Frontiers in Endocrinology, 2023)
Background: SARS-CoV-2 infection during pregnancy may cause adverse maternal, neonatal and placental outcomes, but not well-studied. While tissue hypoxia is often reported in COVID-19 patients, pregnant women with anemia are suspected to be more prone to placental hypoxia-related injuries. Methods: This hospital-based cross-sectional study was conducted between August-November 2021, during COVID-19 second wave in India. Term pregnant women (N=212) were enrolled consecutively from those admitted to hospital for delivery, where hospital admission mandated testing RT-PCR negative for SARS-CoV-2 virus and absence of active infection. Data on socio-demography, COVID-19 history, maternal, obstetric, and neonatal outcomes were recorded. Pre-delivery maternal and post-delivery cord blood samples were tested for hematological parameters and SARS-CoV-2 antibody. Post-delivery placentae were studied for histology. Results: Of 212 women, 122 (58%) were seropositive for SARS-CoV-2 IgG, but none reported COVID-19 history; 134 (63.2%) were anemic. In seropositive women, hemoglobin (p=0.04), total WBC (p=0.009), lymphocytes (p=0.005) and neutrophils (p=0.02) were significantly higher, while neutrophils to lymphocytes (p=0.12) and platelets to lymphocytes ratios (p=0.03) were lower. Neonatal outcomes were similar. All RBC parameters were significantly lower in anemic mothers but not in cord blood, except RDW that was significantly higher in both, maternal (p=0.007) and cord (p=0.008) blood from seropositive anemic group compared to other groups. Placental histology showed significant increase in villous hypervascularity (p=0.000), dilated villous capillaries (p=0.000), and syncytiotrophoblasts (p=0.02) in seropositive group, typically suggesting placental hypoxia. Maternal anemia was not associated with any histological parameters. Univariate and multivariate logistic regression analyses of placental histopathological adverse outcomes showed strong association with SARS-CoV-2 seropositivity but not with maternal anemia. When adjusted for several covariates, including anemia, SARS-CoV-2 seropositivity emerged as independent risk factor for severe chorangiosis (AOR 8.74, 95% CI 3.51-21.76, p<0.000), dilated blood vessels (AOR 12.74, 95% CI 5.46-29.75, p<0.000), syncytiotrophoblasts (AOR 2.86, 95% CI 1.36-5.99, p=0.005) and villus agglutination (AOR 9.27, 95% CI 3.68-23.32, p<0.000). Conclusion: We observed that asymptomatic COVID-19 during pregnancy seemed to be associated with various abnormal placental histopathologic changes related to placental hypoxia independent of maternal anemia status. Our data supports an independent role of SARS-CoV-2 in causing placental hypoxia in pregnant women.